Food Wastage sebagai Ancaman Ketahanan Pangan: Strategi Preventif Berbasis Hadis: Krisis Food Wastage dalam Ketahanan Pangan Global; Analisis Hadis-hadis Pencegahan Pemborosan Makanan; Strategi Preventif Hadis dalam Upaya Mitigasi Krisis Pangan - Azizah Fauziyah Hamid; Arifuddin Ahmad; La Ode Ismail Ahmad (Al-Mu'tabar, 2026)
The phenomenon of food wastage has transformed into a serious threat to global food security, which ultimately has a massive impact on various aspects, especially the economy and the environment. As one of the countries with the largest Muslim population, Indonesia ranks 8th in the world as the largest contributor to household food waste. This article aims to formulate preventive strategies to combat food waste by exploring the prophetic values contained in the hadiths of the Prophet Muhammad saw. This study uses a qualitative method through literature review, where data collection was conducted using the takhrij al-hadith technique to ensure the originality of the hadith texts. At the same time, the thematic syarh al-hadith technique was used to examine the meaning of the hadith. Results of the study indicate that the Prophet's hadiths offer three comprehensive mitigation strategies, as follows: paradigm transformation through the principle of moderation in consumption to prevent wasteful behavior; implementation of zero-waste micro-ethics by valuing food scraps or dropped bites; and managerial protection of resources to prevent wasteful behavior. The findings in this article emphasize that the prophetic values contained in the hadith are capable of providing more applicable technical guidance to deconstruct lifestyles that tend to be consumptive and driven by arrogance. Article recommends the internalization of prophetic manners as a moral basis in strengthening national food security for the realization of complete benefit.